Sintesis Coating Copper-Cobalt Oksida Pada Substrat Aluminium Melalui Proses Sol Gel Sebagai Solar Selective Absorber : Pengaruh Rasio Molar Cu/Co Dan Ketebalan Coating - Peter Peter; Amun Amri; Ahmad Fadli (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Solar selective absorber (SSA) is a layer which is selective to absorb solar radiation and convert it into maximum heat energy. The purpose of this research is to synthesize the SSA based on copper nitrate and cobalt nitrate precursor, to determine the influence of molar ratio and dipping times number to absorptance, and emittance of SSA using the sol gel dip coating method.. Aluminum plates with size of 2x4cm2 were cleaned using phosphoric acid 10% by volume at temperature ±50oC for 10 minutes and then washed again with distilled water. Sol precursor was prepared by mixing copper nitrate and cobalt nitrate in ethanol solvent and the addition of propionic acid as catalyst and complexing agent. This solution was stirred at room temperature for 2 hours. The coatings were synthesized by varying molar ratio of [Cu]/[Co] of 0,25; 1; and 4 with the number of dipping 1-10 times. The coatings then were annealed at temperature of 550oC for 1 hour. Reflectance spectra in the UV-Vis-NIR show that an increasing number of dipping and decreasing in the molar ratio of [Cu]/[Co] improved the absorptance (). SSA layer with best absorptance i.e. 84,788% is synthesized using precursors with a molar ratio of 4 at 10 dipping times, and emittance (ε) generated amount 8,999%.Keywords : aluminum, dip coating, solar selective absorber.